Analisis Strategi Implementasi Teknologi dalam Pendidikan - Djusran Bachtiar; Erlina Neni Indriyani; Erna; Erviani; Faisal; Andi Warisno; Nila Wati Tajuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of information and communication technology demands a fundamental transformation in education. Technology implementation is no longer just an option but a crucial strategy to enhance learning efficiency, accessibility, and quality. However, technology integration often faces technical constraints, human resource readiness, and uneven infrastructure. Therefore, a structured and comprehensive technology implementation strategy is required to ensure its utilization is optimal and sustainable. This article examines technology implementation strategies in education, covering planning aspects, human resource capacity building, infrastructure provision, and periodic evaluation. Through appropriate implementation strategies, educational institutions can optimize the digital ecosystem, expand access to learning materials, enhance pedagogical interactions, and prepare students with 21st-century competencies. The success of this implementation relies heavily on adaptive policy synergy and the commitment of all stakeholders.